Pemanfaatan Business Intelligence Dalam Pembuatan Strategi dan Pengambilan Keputusan Bisnis - Achmad Fauzi; Aditya Aji Nugroho; Anselinus Kevin Monte; Audri Angelia Ignesia; Muhammad Nafis Makruf; Roganda Andreas; Siti Rahmah Nur Hasanah (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
Business Intelligence (BI) Business Intelligence is a very important component in the business world, especially in terms of consolidation, analysis, storage and access of data which is very important for Karma's business continuity. Business intelligence helps make sound business decisions and maintain business continuity, as well as develop business strategies and understand a company's position in a large market. This study uses qualitative research methods where data is collected from various sources such as books, journals, articles and other references. The qualitative method was chosen because this research will deepen information about the business intelligence decision-making process in companies. To achieve the best business decisions, several processes must be followed, namely making decisions that are realistic and can be implemented within the deadline, gathering relevant information and finding relevant alternative solutions. All in all, business intelligence plays a vital role in improving a company's business through the use of relevant data. BI systems also support decision making to save time, costs and reduce human error. Many companies use BI systems in their business because they realize their benefits in making effective decisions.